1993
DOI: 10.1038/clpt.1993.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grapefruit juice and naringin on nisoldipine pharmacokinetics

Abstract: The bioavailability of some dihydropyridine calcium antagonists can be markedly augmented by grapefruit juice and may involve the bioflavonoid naringin. The pharmacokinetics of nisoldipine coat-core tablet were studied in a Latin square-designed trial in which 12 healthy men were administered the drug with water, grapefruit juice, or encapsulated naringin powder at the same amount as that assayed in the juice. Compared with water, grapefruit juice increased the maximum concentration of nisoldipine to 406% +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(80 citation statements)
references
References 2 publications
2
77
0
1
Order By: Relevance
“…Most of these studies reported further decreases in diastolic blood pressure when felodipine was taken with grapefruit juice, as well as increase in haemodynamic-related adverse effects such as increased heart rate and orthostatic hypotension (Bailey et al, 1991;Lundahl et al, 1997Lundahl et al, , 1998. Other dihydropyridines exhibiting the interaction to a similar extent are nisoldipine (Bailey et al, 1993b;Takanaga et al, 2000) and nicardipine . A milder but significant interaction has been detected with nitrendipine, pranidipine and nimodipine that exhibited bioavailability increments of 100, 73 and 50%, respectively (Soons et al, 1991;Fuhr et al, 1998;Hashimoto et al, 1998).…”
Section: Amounts and Timingmentioning
confidence: 95%
See 1 more Smart Citation
“…Most of these studies reported further decreases in diastolic blood pressure when felodipine was taken with grapefruit juice, as well as increase in haemodynamic-related adverse effects such as increased heart rate and orthostatic hypotension (Bailey et al, 1991;Lundahl et al, 1997Lundahl et al, , 1998. Other dihydropyridines exhibiting the interaction to a similar extent are nisoldipine (Bailey et al, 1993b;Takanaga et al, 2000) and nicardipine . A milder but significant interaction has been detected with nitrendipine, pranidipine and nimodipine that exhibited bioavailability increments of 100, 73 and 50%, respectively (Soons et al, 1991;Fuhr et al, 1998;Hashimoto et al, 1998).…”
Section: Amounts and Timingmentioning
confidence: 95%
“…In addition, in studies that were performed on liver microsomes, naringenin, naringin's aglycon metabolite, showed the ability to inhibit dihydropyridine metabolism in vitro (Miniscalco et al, 1992). However, in vivo studies using isolated naringin have not shown reduced metabolism of CYP3A4 substrates (Bailey et al, 1993b). Also, grapefruit juice itself shows inhibition in vitro under conditions that do not allow the formation of naringenin (Edwards & Bernier, 1996).…”
Section: Constituentsmentioning
confidence: 99%
“…Moreover, these models do not relate to blood flow, drug partitioning, and the phenomenon of route-dependent intestinal metabolism. A greater understanding of the interplay will allow sound interpretations on intestinal drug metabolism and transport with respect to other drugs or the intake of fruit juices (Bailey et al, 1993;Lown et al, 1997a;Dresser et al, 2002).…”
Section: Fig 4 Fits Of Tracer [ 3 H]morphine Data From the Vascularmentioning
confidence: 99%
“…15) In fact, unlike GJ, naringin, a potent, but not mechanism-based inhibitor of CYP3A, 21) has been reported not to increase the availability of nisoldipine in humans. 26) The present investigations clearly showed the contributions of FCs on drug interactions with GJ in in vitro and in vivo experiments using GJ samples, eliminated BG and DHB following high temperature treatments. Furthermore, these observations may develop as fundamental knowledge to create "drinkable GJ" for patients receiving medications that induce interactions with GJ.…”
Section: Measurement Of Fcs In Gjmentioning
confidence: 86%